2012
DOI: 10.1590/s0074-02762012000700004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of Plasmodium falciparum Welch field isolates to infusions prepared from Artemisia annua L. cultivated in the Brazilian Amazon

Abstract: Artemisinin is the active antimalarial compound obtained from the leaves of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
17
2
Order By: Relevance
“…The overall extraction efficiency of this study was however quite low (7.27% for 12 h, 4.51% for 2 h compared to 53.8% for the dried leaves infusion) (Wright et al, 2010). Silva et al (2012) on the other hand observed high extraction efficiencies of 78-91% after boiling the dried leaves with no squeezing which are similar to those of Räth et al (2004). Van der Kooy and Verpoorte (2011) studied the extraction efficiency of artemisinin at different temperatures and found as expected that with increasing temperatures the extraction efficiency of artemisinin increased.…”
Section: Extraction Efficiency and Stability Of Artemisinincontrasting
confidence: 53%
See 1 more Smart Citation
“…The overall extraction efficiency of this study was however quite low (7.27% for 12 h, 4.51% for 2 h compared to 53.8% for the dried leaves infusion) (Wright et al, 2010). Silva et al (2012) on the other hand observed high extraction efficiencies of 78-91% after boiling the dried leaves with no squeezing which are similar to those of Räth et al (2004). Van der Kooy and Verpoorte (2011) studied the extraction efficiency of artemisinin at different temperatures and found as expected that with increasing temperatures the extraction efficiency of artemisinin increased.…”
Section: Extraction Efficiency and Stability Of Artemisinincontrasting
confidence: 53%
“…The results of these experiments were confirmed with in vivo tests performed in mice where it was found that a dose of 18 mg/kg of artemisinin in planta suppressed parasitaemia by 95% while a 30 mg/kg dose of pure artemisinin suppressed the paraesatemia by 88%. Silva et al (2012) tested the effectiveness of the tea infusion against field isolated Plasmodium falciparum which were resistant to chloroquine. The infusions were determined to be an effective low toxicity treatment against chloroquine-resistant Plasmodium falciparum, having an IC 50 of 0.11-0.14 mg/mL, however no synergistic effects were noted and thereby contradicting the results reported by De Donno et al (2012) and Wright et al (2010).…”
Section: Identification Of Other Compounds In the Artemisia Annua Formentioning
confidence: 99%
“…Furthermore, the dose of 400 kg ha -1 of silicate induced higher concentrations of artemisinin than those previously reported in plants without the application of silicate (94.0 μg mL -1 ; Mueller et al, 2004 ; Räth et al, 2004 ). Clearly, these results show wide variation in the artemisinin content in A. annua infusion samples, indicating that many factors, such as temperature, contact time, percentage of material, solvent, and plant genetics can influence the solubility of artemisinin and its subsequent therapeutic effects ( van der Kooy and Verpoorte, 2011 ; Rocha e Silva et al, 2012 ). In this context, it is likely that the unexpected very low concentrations of artemisinin in infusion samples, which were obtained from A. annua treated with 1600 kg ha -1 and, especially with 800 kg ha -1 of silicate, may have been affected by some of these factors, which may impact the solubility of artemisinin, resulting in almost undetectable levels.…”
Section: Discussionmentioning
confidence: 93%
“…Parasite inhibition was expressed as a percentage of the growth of untreated (negative) controls. All assays were performed in triplicate [ 45 ]. Extracts that inhibited parasite growth by ≥80 % at concentrations of 50 μg/mL were further evaluated using the procedure described below.…”
Section: Methodsmentioning
confidence: 99%